Circulating myomiRs: a new class of biomarkers to monitor skeletal muscle in physiology and medicine. Issue 1 (28th November 2017) - Siracusa, Julien; Koulmann, Nathalie; Banzet, Sébastien
Abstract: MicroRNAs (miRNA) are small non‐coding RNAs that target mRNAs and are consequently involved in the post‐transcriptional regulation of gene expression. Some miRNAs are ubiquitously expressed in tissue, while others are tissue‐specific or tissue‐enriched. miRNAs can be released by cells and are found in various biofluids, including serum and plasma. Thus, measuring miRNAs in the circulation may provide information on the originating tissue or cells. MyomiRs are described as striated muscle‐specific or muscle‐enriched miRNAs. Their circulating levels can be measured and have been proposed to be new biomarkers of physiological and pathological muscle processes. The aims of this review are to summarize the current knowledge of circulating myomiRs, to identify the types of information they can provide about skeletal muscle, and to determine how to apply that information in the fields of research and medicine.